Islamic Parenting Methods After the Pandemic in Strengthening Children's Mental Learning in Kotarih Baru Village Serdang Bedagai Regency - Paujiah, Nurleli; Nurhanifah, Nurhanifah; Saragi, Muhammad Putra Dinata (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2023)
This study aims to identify Islamic parenting methods in strengthening children's mental learning, identify parents' mental reinforcement of children's learning and also parents' obstacles to children in implementing Islamic parenting methods in Kotarih Baru Village, Serdang Bedagai district.This research is a type of qualitative research using field research methods. The data collection techniques in this study, namely by using observation, interviews, and documentation. The subjects in this study were five families with a total of 15 people. Data analysis techniques, namely data reduction, data presentation, drawing conclusions and verification. The results of the research regarding the Islamic Parenting Method are providing knowledge according to Islamic teachings and school teachings, praying, reading the Koran, stories of the Prophet, instilling faith, reciting the Koran. The parenting methods provided are discipline and exemplary methods, methods of giving gifts and rewards, and story method. Obstacles for parents in implementing Islamic Parenting methods are addiction to playing gadgets, socializing with friends, parents' lack of understanding of religion.